2012
DOI: 10.1159/000339731
|View full text |Cite
|
Sign up to set email alerts
|

Less Cognitive and Neurological Deficits in Schizophrenia Patients Carrying Risk Variant in <b><i>ZNF804A</i></b>

Abstract: Background: The rs1344706 single nucleotide polymorphism in the ZNF804A gene is a common variant with strong evidence for association with schizophrenia. Recent studies show an association of rs1344706 with cognitive functioning, and there is some evidence suggesting that the risk allele may increase susceptibility for a subtype of schizophrenia with relatively spared cognition. Methods: We tested the effect of rs1344706 genotype in 89 schizophrenia patients on 3 basic cognitive domains (working memory, proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 103 publications
2
7
0
1
Order By: Relevance
“…These findings are consistent with a number of other neuropsychological studies of ZNF804A published since then in which risk allele carriers outperform noncarriers, 15,16,37 though not all. 17,18 Earlier findings from our lab indicated that the ZNF804A risk allele was associated with relatively preserved cognitive functioning in patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are consistent with a number of other neuropsychological studies of ZNF804A published since then in which risk allele carriers outperform noncarriers, 15,16,37 though not all. 17,18 Earlier findings from our lab indicated that the ZNF804A risk allele was associated with relatively preserved cognitive functioning in patients.…”
Section: Discussionsupporting
confidence: 91%
“…Our interpretation of these findings was that ZNF804A may be particularly associated with an illness subtype in which cognitive and associated grey matter deficits are less prominent. Although a number of studies have since supported this view 15,16 others have not, 17,18 or they have suggested that ZNF804A may instead have a deleterious impact on aspects of social cognition. 19,20 …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, studies investigating the polymorphism in the ZNF804A gene (rs1344706), known to upregulate genes implicated in the TGF-β signaling,10 have shown its correlation with several domains of cognitive performance including episodic and working memory, executive functions, verbal learning, and recall 5761. Most interestingly, the ZNF804A gene polymorphism (rs1344706) has been found to predict poorer executive control of attention in schizophrenia, overlapping partially with the results of our study 60.…”
Section: Discussionsupporting
confidence: 85%
“…Further studies have linked ZNF804A to neurocognitive measures including verbal working memory and episodic working memory (e.g., Walters et al, 2010). However, within schizophrenia cases, the schizophrenia-associated risk allele has shown relatively preserved cognition (Walters et al, 2010; Becker et al, 2012; Van Den Bossche et al, 2012; Chen et al, 2012), whereas in healthy controls the same schizophrenia-associated risk allele appears to impart poorer performance (Lencz et al, 2010; Esslinger et al, 2011; Voineskos et al, 2011; Balog et al, 2011). The SNP in our study, rs1366842, is approximately 10kb from rs1344706 and is in modest linkage disequilibrium with this SNP (HapMap, CEU and TSI populations, r 2 = 0.40).…”
Section: Discussionmentioning
confidence: 99%